Apakah Profitabilitas Bank Syariah Didorong oleh Faktor Internal? - Laili Maghfiroh; Nur Hajijah; Zainal Musthafa; Umrotul Khasanah (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
The purpose of this study is to review and analyze the factors that influence the profitability of Islamic banks in Indonesia. The approach method used in this research is a quantitative approach. The data needed for this research is secondary data which is a report from the Annual Sharia Banking Statistics for the period 2018-2020 obtained and obtained from the Financial Services Authority. Using multiple linear regression analysis techniques (multiple linear regression method). The results show CAR, NPF, FDR and BOPO have a simultaneous influence on the profitability (ROA) of Islamic commercial banks in Indonesia for the 2018-2020 period, and CAR, NPF, and FDR partially have no effect on the profitability (ROA) of Islamic commercial banks in Indonesia for the 2018-2020 period and BOPO partially has a significant negative effect on the profitability (ROA) of Islamic commercial banks in Indonesia for the 2018-2020 period. This research is limited by internal factors that affect the profitability of Islamic commercial banks in Indonesia.